PENGARUH HEALTH LITERACY TERHADAP PENGETAHUAN PENDAMPING MENELAN OBAT PASIEN TUBERKULOSIS DI BENGKULU - Titi A; Titin Aprilatutini; Feni Eka Dianty; Nova Yustisia (JURNAL PENELITIAN TERAPAN KESEHATAN, 2021)
Problems: The achievement of the prevalence of pulmonary TB in Bengkulu is not yet optimal, it is still a health problem for the community. Province ranks first with 17,419 cases, while Bengkulu City ranks first with 334 souls. The independence of companions to the treatment of tuberculosis patients is very important in the tuberculosis treatment and care program at home. The aim of the research to analyze the effect of health literacy on drug swallowing assistance (PMO) for tuberculosis patients. Research method: Research design "quasy experiment". The population was all PMO tuberculosis patients who underwent a 1-2 month treatment program at the Nusa Indah Public Health Center, Sukamerindu, Small Bridge, Muara Bangkahulu and Bengkulu City Fish Market as many as 80 people. Samples were taken using purposive sampling technique and were divided into treatment groups (40 people) and control groups (40 people). The independent variable is health literacy. The dependent variable is PMO independence. The instruments in the study were questionnaires and observation sheets. The first step is that the researcher obtains the identity of the respondent and then conducts a pre-test to assess the independence of the PMO before conducting health literacy. After that, according to the agreement, the researcher made a home visit for 1 time in the first month after that the treatment was for 1 week, then in the 3rd month the researcher conducted a post test. Research data processing using SPSS version 25. Previously, the instrument was tested on the modified PMO independence questionnaire with a reliability value of r table 0.220 and a Chronbach r alpha value of 0.764 which means reliable. The value of the r validity test is 0.771 where r is greater than r table so that the keyword is valid. Then analyzed using ANOVA at a significant level of 0.05. Results: showed that there was a significant effect of health literacy on PMO knowledge (p=0.000). Conclusion: knowledge is an important element in the independence of PMO and the success of tuberculosis patients in treatment. Future researchers are expected to conduct research with other variables such as quality of life of pulmonary tuberculosis patients and more samples.Keywords: health literacy, knowledge, tuberculosis